Surgical management of middle ear cholesteatoma and reconstruction at the same time (Colombia Medica, 2014)
Introduction. The surgical management of cholesteatoma. You can opt for a closed technique (mastoidectomy simple) or open surgery (radical mastoidectomy). The open mastoidectomy with reconstruction of the posterior wall of the middle ear reconstruction in one surgery combines the advantages of both techniques as adequate surgical exposure, eradication of cholesteatoma and anatomical reconstruction of the middle ear structures. Objective. To evaluate the surgical results in the management of cholesteatoma with the technique of open mastoidectomy with reconstruction of the posterior wall and the middle ear in one surgery. Methods. Prospective analytical observational study conducted between 2009-2012 with patients undergoing this surgical technique in the Hospital Universitario del Valle, performing preoperative clinical monitoring and quarterly postoperative tomography and previous assessments of hearing and pre -and postoperative audiometry. Results. 45 patients were studied. Mean Postoperative follow-up was 28 months. Surgical success was achieved in 93.3% of patients as measured by clinical and radiological follow. Hearing preservation was found after reconstruction of the hearing mechanism, based on measured audiometry auditory tone average (PTA) by the statistical test for paired samples between preoperative and postoperative PTA. (95% CI -1.47 to 12.15). Residual cholesteatoma was presented in 6.6%, three to four times lower than that reported in the literature. Conclusions. This type of surgery can be considered a successful technique in the treatment of cholesteatoma in selected cases.